2021
DOI: 10.1101/2021.08.16.456548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precision engineering of an anti-HLA-A2 chimeric antigen receptor in regulatory T cells for transplant immune tolerance

Abstract: Infusion of regulatory T cells (Tregs) engineered with a chimeric antigen receptor (CAR) targeting donor-derived human leukocyte antigen (HLA) is a promising strategy to promote transplant tolerance. Here, we describe an anti-HLA-A2 CAR (A2-CAR) generated by grafting the complementarity-determining regions (CDRs) of a human monoclonal anti-HLA-A2 antibody into the framework regions of the Herceptin 4D5 single-chain variable fragment and fusing it with a CD28-zeta signaling domain. The CDR-grafted A2-CAR mainta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…The complementarity determining regions of the anti‐HLA‐A2 scFv from a human B‐cell‐derived hybridoma (clone SN607D8) were grafted onto the framework of Herceptin/trastuzumab (clone 4DG) as previously described 14 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The complementarity determining regions of the anti‐HLA‐A2 scFv from a human B‐cell‐derived hybridoma (clone SN607D8) were grafted onto the framework of Herceptin/trastuzumab (clone 4DG) as previously described 14 …”
Section: Methodsmentioning
confidence: 99%
“…The complementarity determining regions of the anti-HLA-A2 scFv from a human B-cell-derived hybridoma (clone SN607D8) were grafted onto the framework of Herceptin/trastuzumab (clone 4DG) as previously described. 14 To generate an anti-HLA-A2 murine CAR, the grafted scFv was cloned in-frame to the murine CD8 hinge and transmembrane domains followed by CD28 and CD3ζ intracellular domains via isothermal DNA assembly. The A2-CAR was cloned into a murine stem cell virus-based retroviral vector with an N-terminal myc tag and in-frame to a truncated EGFR (EGFRt), separated by a P2A peptide.…”
Section: Car Generation and Retrovirus Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the authors found that engineered Treg selectively traffic to HLA-A2 expressing transplanted islet cells, thereby underscoring their ability to recognize their cognate antigen in vivo. 80 Their study outlined the need for engineering highly specific Treg without disrupting their functionality by introduction of a single HLA-antigen-specific CAR. Removal of the endogenous TCR and demonstration of stability of Treg function in vivo encourage the potential use of "off-the-shelf" Treg for the treatment of rejection reaction in transplant patients.…”
Section: Car-treg In Transplantationmentioning
confidence: 99%